Formação integral nos cursos da área da saúde: contribuição para humanização na educação superior - Rodenbusch, Camila de Barros (2019)
This thesis addresses the theme of humanization in higher education in health. The research meets the proposal presented by the United Nations Educational, Scientific and Cultural Organization (UNESCO) of a “Global Citizenship Education”, requiring students to be prepared to face the challenges present in society, seeking to develop socio-emotional skills, human values and fundamental attitudes to promote social transformation, making them professionals concerned with society and people. The objective was to analyze the perception of undergraduate health professors about integral education and to present elements for a humanizing teaching practice. It is a qualitative, descriptive study with a case study approach. The participants are teachers of the undergraduate courses in health, from a community institution of Higher Education, located in the state of Rio Grande do Sul. To meet the objectives of this research, a questionnaire and a semi-structured interview were used for data collection. The questionnaire data were analyzed and presented descriptively and the data from the Semi-Structured Interview were analyzed according to the content analysis technique proposed by Bardin (2011). The theoretical framework that guided the study was divided into three subchapters: Humanist Movement, focusing on Humanist Psychology and Positive Psychology; Humanization in health, encompassing the National Humanization Policy; and, Higher Education emphasizing Integral Training and Teaching Educational Practice. Through the collected data it was possible to verify that the teachers have the understanding of integral formation and humanization according to the theories and the authors approached in the theoretical framework. For them, this training must include the technical aspects, but also the aspects related to the development of the human being as a whole. The curricula of the courses do not yet contemplate these aspects, they are fragmented, reinforcing the technical knowledge. There is a need for innovative and interdisciplinary curricula. It was possible to verify the presence and understanding of the human dimension by the teachers. It is necessary that the courses propose actions of integration between the areas of formation, encompassing human aspects, planning activities that develop the formation for global citizenship. After the analyzes, the thesis reinforces that it is possible to develop an integral and humanized formation in Higher Education.